Correlation Between Attitude and Self-Efficacy with High-Order Thinking Skills of Grade 7 Students at SMP Negeri 2 Parepare in Science Subjects for the Even Semester - risnatia; Anugra, Novia (UNIVERSITAS NEGERI MEDAN, 2025)
This study aims to determine the attitudes, self-efficacy, and high-order thinking skills (HOTS) of seventh-grade students at SMPN 2 Parepare in science subjects in the even semester, as well as to analyze the extent of the relationship between these variables. This study is quantitative research with a correlational approach. Data were obtained through attitude and self-efficacy questionnaires that had been tested for validity and reliability, as well as science learning achievement tests taken from students' final exam results, which had been categorized according to HOTS indicators. The research sample consisted of 115 students. Data analysis includes validity and reliability tests, descriptive analysis, prerequisite tests (normality, linearity, and heteroscedasticity), as well as simple Pearson correlation tests and multiple correlation tests. The results of the descriptive analysis show that the majority of students' attitudes are in the moderate category (66.96%), the majority of students' self-efficacy is also in the moderate category (67.83%), while the majority of students' high-order thinking skills are in the low category, with the analysis aspect being in the high category (40.9%), the evaluation aspect being in the very low category (40%) and the creation aspect being in the very low category (51.3%). The results of the correlation test show that there is a negative and significant correlation between attitudes and high-order thinking skills (r = -0.463; p < 0.05) with a moderate level of relationship, there is a positive and significant correlation between self-efficacy and high-order thinking skills (r = 0.309; p < 0.05) with a low level of relationship, and attitudes and self-efficacy simultaneously have a very high correlation with high-order thinking skills (r2 = 0.848; p < 0.05).